An audit of paediatric dental patient assessment and recall in Faculty of Dentistry UiTM Sungai Buloh/ Aimi Shafiqah Shukri, Muhammad Syazwan Hassan, Annapurny Venkiteswaran - Shukri, Aimi Shafiqah; Hassan, Muhammad Syazwan; Venkiteswaran, Annapurny (2019)
Objective: To assess if the recall appointments and the use of radiographs for paediatric dental patients at Faculty of Dentistry, UiTM comply with current guidelines. Materials and Method: A retrospective study was conducted using patients' dental records that were registered at the Faculty of Dentistry UiTM. The sample consisted of 350 randomly chosen treatment records of paediatric patients aged between birth and 16 years of age at the time of data collection which was in the year 2016. Data collection included demographic details, whom the cases were treated by, caries risk assessment, radiographs taken and time taken for the patient's review appointments. Results: An initial sample size of 350 records were assessed. The mean age of patients seen when they were first seen is 6.3 years old. Caries Risk Assessment was not reported in majority of the cases (58%,). Baseline radiographs were taken in 44.6% of the cases. For the assessment of recall attendance, only samples with data on CRA was analysed (n=145). The review appointments at 3 months interval was 70% whereas at 6 months was 6.2% and one year recall was 6.7%. A chi-square test showed significant difference (p=0.013) between the category of operators for the 1-year review whereby review was higher among students and specialists as compared to dental officers. Conclusion: This study shows poor adherence to the recommended recall protocol as suggested by NICE and AAPD guidelines. Further studies need to be done to assess the patients' and clinicians awareness regarding the recall protocol and determine the problems causing poor recall attendance.